Bioactive Indole Derivatives from the South Pacific Marine Sponges Rhopaloeides odorabile and Hyrtios sp. - Longeon, Arlette (Molecular Diversity Preservation International, 2011)
Indole derivatives including bromoindoles have been isolated from the South Pacific marine sponges Rhopaloeides odorabile and Hyrtios sp. Their structures were established through analysis of mass spectra and 1D and 2D NMR spectroscopic data. Their potential inhibitory phospholipase A(2) (PLA(2)), antioxidant and cytotoxic activities were evaluated. The new derivative 5,6-dibromo-l-hypaphorine (9) isolated from Hyrtios sp. revealed a weak bee venom PLA(2) inhibition (IC(50) 0.2 mM) and a significant antioxidant activity with an Oxygen Radical Absorbance Capacity (ORAC) value of 0.22. The sesquiterpene aureol (4), also isolated from Hyrtios sp., showed the most potent antioxidant activity with an ORAC value of 0.29.